An analysis of incomplete contacts in partial slip - Ramesh, R (2018)
Fretting fatigue is often the cause of failure in many engineering components. It is of importance in safety critical components subject to extreme loads such as in dovetail joints in jet engines. In order to accurately estimate the life of these components, accurate knowledge of the shear traction and differential strains at the contact interface is required. The loading that these components are subjected to is often complicated (varying normal load, bulk tension and shear force) and needs to be simplified, to ignore the variation in either the bulk tension or the normal load. The aim of this thesis is to develop a method which estimates the extent and magnitude of slip in incomplete contact problems where the normal load, shear force and bulk tension vary with time. Three new methods are first presented to solve incomplete contact problems in partial slip. One of these methods - using a dislocation correction to the fully stuck solution - is used to study problems where the normal load is held constant. Then, the problem of a varying normal load and bulk tension is studied in detail using the existing method of a traction correction to the sliding solution. Finally, the distributed dislocation method is used to solve the most general problem involving an incomplete problem with a varying normal load, bulk tension and shear force.